Two new species of Phalangium (Opiliones: Phalangiidae) from Turkey - Kurt, Kemal; Erdek, Melek; Kurt, Pinar (Zootaxa, 2023)
Two new harvestmen species, Phalangium nalanae sp. n. and Phalangium taylani sp. n., are described, diagnosed and illustrated based on male material from Hakkari Province, Turkey. Also, the differences between two new species and similar species of the genus Phalangium are discussed.